Investigate the Thermal Effects on Flow Resisting Properties of Hydrocarbons in a Pipeline [EXPERIMENT] - Wan Izzul Fathi Bin Hamdan, Wan Izzul Fathi (Universiti Teknologi Petronas, 2012)
Pipelines are among the most important element in oil and gas industry and can be located on either onshore or offshore depending on the project requirements. Pipelines are either buried or placed on the ground (seabed for offshore applications) and can reach up to hundreds and thousands of kilometers. One of the problems that are faced in pipelines is its flow assurance when the medium being transported in the pipelines acquire a flow resisting properties. Oil companies face these inevitable problems frequently because of the nature of the hydrocarbon itself. Most of the flow resisting hydrocarbons are paraffinic oil that contains wax (also known as heavy crude). One of the factors that contribute to blockage in pipelines is when this heavy crude encounter low temperature region in the pipeline. Wax depositions will cause pressure drops across the pipeline, causing low production rate at the receiving end. It is known that the heavy crude will react to difference in temperature thus this project will investigate the thermal effect on the flow resisting properties of hydrocarbons in a pipeline. This project aims at studying the thermal interactions between the production lines and heating lines to prevent the deposition of wax in the pipeline. This dissertation report will cover the introductions, literature review, research methodology, results, discussions, recommendations and the conclusion of the project